Kinetic effects on the 660-km-phase transition in mantle upstreams and seismological implications. Issue 2 (31st May 2022) - Lessing, Stephan; Dobson, David P; Rost, Sebastian; Cobden, Laura; Thomas, Christine
Summary: The effects of reaction kinetics of bridgmanite and ferropericlase transforming to ringwoodite on elastic properties in upwelling mantle are investigated using data of kinetic experiments and internally self-consistent thermodynamic modelling of density and seismic velocities. The kinetic experiments show inhibited grain growth of ringwoodite. At the initiation of ringwoodite growth, bridgmanite completely transforms to a metastable pyrope-bearing garnet. Ringwoodite then gradually grows from the metastable assemblage of ferropericlase and garnet. The changes in mineralogy result in a low-velocity zone directly above the 660 km seismic discontinuity due to the lower seismic velocities and densities of ferropericlase and garnet compared to ringwoodite and bridgmanite. The modelling of the effects of reaction kinetics and its effect on seismic structure at ∼660 km depth shows more sensitivity to grain size than to temperature and upwelling rate. Modelling 1-D synthetic seismograms of PP (SS) underside reflections off the kinetically inhibited backward reaction to ringwoodite shows advanced traveltimes of underside reflections off ∼660 km depth of 0.2–0.8 s (1.2–1.6 s) for upwelling rates of 50 cm yr –1 and initial grain sizes between 5 and 20 cm due to the low-velocity zone above the 660 km discontinuity. The finite width of the low-velocity layer results in frequency-dependent behaviour of PP and SS underside reflection amplitudes, with higher amplitudes towards shorter periods. The effect on the traveltimes of P-to-s conversions used for receiver function is small (<0.7 s) but the inhibited backward reaction leads to strong amplitude changes and significant waveform variations. The effects of reaction kinetics in mantle upwellings might serve as an additional means to map regions of large-scale upwellings and to constrain grain size in the lower mantle.